Evaluation of Three Okra (Abelmoschus esculentus L. Moench) Varieties in Response to Organic and Inorganic Fertilization - Bristy, Farhana Binte Quyyum; Khan, Sabia; Islam, Md. Morshedul; Anjum, Kazi Ishrat (Fundamental and Applied Agriculture, 2024)
A field experiment was conducted during the Kharif-2 season of 2022 at Noakhali Science and Technology University to examine the impact of organic and inorganic fertilizers on the growth and yield of okra. A factorial experiment involving two factors was implemented. Factor A consisted of three varieties of okra viz., V1- Green Finger, V2- BARI Dherosh-1, V3- a local variety, along with factor B consisted of three treatments viz., T1- Organic fertilizers (Vermicompost @ 5 t/ha + Farmyard Manure @ 5 t/ha), T2- Chemical fertilizers (NPK: 80:60:60 kg/ha), and T3- Control. The experiment was laid out in a Randomized Complete Block Design with three replications. Data were collected on different vegetative and yield parameters. Results revealed that the Green Finger variety exhibited higher growth and yield in comparison to both the BARI Dherosh-1 and the local variety. The organic fertilizer treatment demonstrated greater outcomes in contrast with chemical fertilizers and without fertilizer. Therefore, the treatment combination V1T1, consisting of the Green finger variety with a Vermicompost @ 5 t/ha + Farmyard Manure @ 5 t/ha, resulted in the maximum okra production of 14.15 tons/ha. The experiment's findings led to the inference that the utilization of vermicompost and FYM in combination is an effective organic fertilizer in comparison to chemical fertilizers. Therefore, it is imperative to promote the appropriate utilization of organic sources of nutrients in the production of okra to enhance growth and increase production.